Ultrasound image enhancement: A review (2012)
Medical ultrasound imaging uses pulsed acoustic waves that are transmitted and received by a hand-held transducer. This is a mature technology that it is widely used around the world. Among its advantages are that it is cost-effective, flexible, and does not require ionizing radiation. However, the image quality is affected by degradation of ultrasound signals when propagating through biological tissues. Many efforts have been done in the last three decades to improve the quality of the images. This paper reviews some of the most important methods for ultrasound enhancement. We classified these techniques into two groups: preprocessing and post-processing, analyzed their benefits and limitations, and presented our beliefs about where ultrasound research could be directed to, in order to improve its effectiveness and broaden its applications. © 2011 Elsevier Ltd.